Composition of submarine Fe-Mn deposits from the Atlantic Ocean - Korotkina, O A; Kogarko, Liya N; Bazilevskaya, Elena S; Kurbakova, I V (Supplement to: Korotkina, OA et al. (2010): Geochemistry of Fe-Mn deposits of the Atlantic Ocean (Strakhov Basin, Elena Seamount, and Cape Verde Quadrangle). Translated from Geokhimiya, 2010, 48(12), 1245-1256, Geochemistry International, 48(12), 1166-1176, https://doi.org/10.1134/S0016702910120025, 2010)
Fe-Mn deposits for this research were sampled on the floor of the Atlantic Ocean within the Cape Verde Quadrangle, Elena Seamount, and Strakhov Basin. Samples were analyzed for major components and for Ni, Co, Cu, P, S, and other trace elements by ICP-AES. Common features in distribution of REE (high positive Ce anomalies) were discovered and trends in distribution of elements with depths were revealed. As, Pb, Sr, Co, and Pt tend to accumulate in shallower water areas, whereas Cu and Li are enriched in deeper water areas. The samples were analyzed in compliance with Andreev's classification and their noble metal composition was determined.